The politics of Buddhist organizations in Taiwan: 1989-2003 : safeguarding the faith, building a pure land, helping the poor - Laliberté, André, 1959- (RoutledgeCurzon, 2004)
"The Politics of Buddhist Organizations in Taiwan looks at a relatively unexplored aspect of modern Taiwan: the influence of religion on politics. Although much has been written on the contribution of Christian churches to the debates on self-determination and democratic transition on the island, we know less about the political influence of Buddhist organizations, which claim together to attract over four million adherents." "This book offers a detailed study of three important Buddhist organizations in Taiwan: the Buddhist Association of the Republic of China (BAROC), the Buddha Light Mountain (or Foguangshan) monastic order, and the Buddhist Compassion Relief Tzu Chi Association (or Ciji). It examines their contrasting approaches to three issues: state supervision of religion, the presidential election of 1996, and the establishment of the National Health Insurance." "This study analyzes the factors that explain the diverse paths the three organizations have taken in the politics of Taiwan. It reveals that despite a shared theological background, individual religious leaders interpret their tradition very differently when they believe it constrains the development of their organization and the fulfilling of its goals. Based on an in-depth examination of these organizations' structures and resources, the proposed explanation of Buddhist leaders' behavior offered in The Politics of Buddhist Organizations in Taiwan compels us to question conventional views about the allegedly passive aspect of religious tradition; deference to authority in societies influenced by Confucian culture; or the adverse legacy of authoritarian regimes."--BOOK JACKET.